Antimicrobial resistance profile of methicillin-resistant Staphylococcus aureus isolates in children reported from the ISPED surveillance of bacterial resistance, 2016–2021 - Wu, Xia; Wang, Chuanqing; He, Leiyan; Xu, Hongmei; Jing, Chunmei; Chen, Yinghu; Lin, Aiwei; Deng, Jikui; Cao, Qing; Deng, Huiling; Cai, Huijun; Chen, Yiping; et al. (Frontiers in Cellular and Infection Microbiology, 2023)
Methicillin-resistant Staphylococcus aureus (MRSA) poses a serious threat to public health worldwide. In December 2015, the Infectious Disease Surveillance of Pediatrics (ISPED) program was organized to monitor bacterial epidemiology and resistance trends in children. This retrospective study was conducted from January 2016–December 2021 on patients at eleven ISPED-group hospitals. From 2016–2021, a total of 13024 MRSA isolates were obtained from children. The most common age group for patients with MRSA infection was less than 3 years old, and newborns were an important group affected by MRSA infection. MRSA was most commonly isolated from the lower respiratory, an abscess, a secretion, or blood in neonates and from the lower respiratory, an abscess, or the upper respiratory in non-neonates. All isolates were susceptible to vancomycin and linezolid and resistant to penicillin; additionally, 76.88%, 54.97%, 22.30%, 5.67%, 5.14%, 3.63%, and 1.42% were resistant to erythromycin, clindamycin, tetracycline, levofloxacin, sulfamethoxazole-trimethoprim (TMP-SMX), gentamicin, and rifampin, respectively. Between 2016 and 2021, a significant increase was seen in the levofloxacin- and TMP-SMX-resistance rates (from 5.45% to 7.14% and from 4.67% to 6.50%, respectively) among MRSA isolates, along with a significant decrease in the rates of resistance to erythromycin (from 82.61% to 68.08%), clindamycin (from 60.95% to 46.82%), tetracycline (from 25.37% to 17.13%), gentamicin (from 4.53% to 2.82%), and rifampin (from 1.89% to 0.41%). The antibiotic-resistance rates varied among MRSA isolated from different sources. Because of the high antibiotic resistance rate to clindamycin, this antibiotic is not recommended for empirical treatment of MRSA infections, especially in osteomyelitis.